Kinetic Evaluation of the Inhibition of Acetylcholinesterase for use as a biosensor - R. Bhuvanagayathri; David K Daniel; Gnanasundaram Nirmala (ASEAN Journal of Chemical Engineering, 2020)
The release of pesticides into the environment has increased, and there is a lack of monitoring of these contaminants. Since the conventional methods of monitoring these contaminants are complicated, costly and time-consuming, mechanisms based on acetylcholinesterase inhibition have emerged as simple and rapid tools for such applications. However, theacetylcholinesterase’s effectiveness as a sensing element in such biosensor systems depends on the conditions selected to measure acetylcholinesterase activity and the concentration of substrate or inhibitor, which in turn affect the reaction rates. Therefore, in the present work, the factors affecting the acetylcholinesterase activity were investigated and inhibition experiments were carried out to evaluate the kinetic parameters. The inhibition rate constant for acetylcholinesterase Ki was found to be 1.9 ppm. The kinetic parameter Km was found to be 3.8mM and Vmax was found to be 1.3µM/min from the Eadie-Hofstee plot. The kinetic study using Lineweaver-Burk method showed mixed type of inhibition of acetylcholinesterase with carbofuran.